A New Flow Injection System with Merging-Zone Technique for the Determination of Copper(II) by Neocuproine Reagent in Aqueous Solution - Ahmed Saleh Farhood; Dakhil Nassir Taha (Universitas Gadjah Mada, 2022)
A fast, simple, and high throughput sample merging-zone flow injection design was developed to determine copper(II) in aqueous solution. The procedure is based on the reduction of copper(II) to copper(I) by uric acid followed by a direct reaction with Neocuproine reagent (NC). The orange-yellow complex that forms absorb light at 454 nm. All conditions of the new flow injection unit were investigated. The analytical curve of copper(II) was linear with (r2) value of 0.9978, in the range of 0.4 to 40 mg/L with a detection limit of 0.1 mg/L and a quantification limit of 0.3 mg/L. the molar absorptivity was 1.661 × 105 L/mol cm and the recovery range was between 104.9 and 97%. The homemade acrylic valve was low-cost with zero dead volume and high repeatability (n = 7) with an RSD of 2.31%. The dispersion coefficient values were 1.8,1.62, and 1.31 for the concentrations of 5, 15, and 25 mg/L, respectively. The sample throughput was 69 h–1.